The pleiotropic effects of statins: a comprehensive exploration of neurovascular unit modulation and blood–brain barrier protection - Jia-Cheng Liu; Shuang-Yin Lei; Dian-Hui Zhang; Qian-Yan He; Ying-Ying Sun; Hong-Jing Zhu; Yang Qu; Sheng-Yu Zhou; Yi Yang; Chao Li; Zhen-Ni Guo (Molecular Medicine)
Abstract The blood–brain barrier (BBB) is the most central component of the neurovascular unit (NVU) and is crucial for the maintenance of the internal environment of the central nervous system and the regulation of homeostasis. A multitude of neuroprotective agents have been developed to exert neuroprotective effects and improve the prognosis of patients with ischemic stroke. These agents have been designed to maintain integrity and promote BBB repair. Statins are widely used as pharmacological agents for the treatment and prevention of ischemic stroke, making them a cornerstone in the pharmacological armamentarium for this condition. The primary mechanism of action is the reduction of serum cholesterol through the inhibition of 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase, which results in a decrease in low-density lipoprotein cholesterol (LDL-C) and an increase in cholesterol clearance. Nevertheless, basic and clinical research has indicated that statins may exert additional pleiotropic effects beyond LDL-C reduction. Previous studies on ischemic stroke have demonstrated that statins can enhance neurological function, reduce inflammation, and promote angiogenic and synaptic processes following ischemic stroke. The BBB has been increasingly recognized for its role in the development and progression of ischemic stroke. Statins have also been found to play a potential BBB protective role by affecting members of the NVU. This review aimed to provide a comprehensive theoretical basis for the clinical application of statins by systematically detailing how statins influence the BBB, particularly focusing on the regulation of the function of each member of the NVU. Graphical Abstract